Politik Hukum Islam Pada Bidang Agraria : Analisis Hukum Agraria Masa Khilafah Untuk Pembangunan Hukum Agraria Nasional - Zulkifli Nas; Zidan Tri Luca Aditama (Yayasan Dar Arrisyah Indonesia, 2025)
This study examines Islamic agrarian legal politics and its relevance to the development of Indonesia’s national agrarian law. Using a doctrinal legal research method with a fiqh siyasah approach, the study analyzes agrarian governance in Imam al-Mawardi’s Al-Ahkam al-Sultaniyyah wa al-Wilayat al-Diniyyah, supported by classical fiqh literature and contemporary agrarian law scholarship. The study finds that Islamic agrarian legal politics is founded upon the principle of divine sovereignty, under which Allah is recognized as the ultimate owner of all agrarian resources, while the state and citizens act as trustees responsible for their management and utilization. The findings further show that Islamic law recognizes individual ownership rights while granting regulatory authority to the state to ensure equitable distribution, sustainable resource management, and public welfare. Agrarian governance is directed toward the realization of maqāṣid al-sharī‘ah, including the protection of religion, life, intellect, lineage, property, dignity, and the environment. The study also identifies policy instruments such as iqṭā‘ tamlīk, iqṭā‘ istighlāl, al-ḥimā, and al-irfāq as mechanisms through which the state may promote distributive justice and ecological sustainability. This research contributes to Islamic agrarian legal theory by formulating Islamic agrarian legal politics as a framework that balances individual rights, state authority, and environmental protection for the development of agrarian law reform in Indonesia.